Biomechanical analysis of the "waiter's serve" on upper limb loads in young elite tennis players. Issue 6 (3rd July 2019) - Touzard, Pierre; Kulpa, Richard; Bideau, Benoit; Montalvan, Bernard; Martin, Caroline
Abstract: Waiter's serve (WS) is a specific tennis serve posture frequently observed in young players, and commonly considered as a technical error by tennis coaches. However, biomechanical impact of WS is unknown. The aims of this study were to identify the potential consequences of WS in young elite players relating to performance and injury risk, and to explain the kinematic causes of WS. Serve of 18 male junior elite players (Top 10 national French ranking, aged 12–15 years) was captured with a 20 camera, 200 Hz VICON MX motion analysis system. Depending on their serve technique, the players were divided into two groups (WS versus Normal Serve [NS]) by experienced coaches. Injury data were collected for each player during a 12-month-period following the motion capture. Normalized peak kinetic values of the dominant arm were calculated using inverse dynamics. In order to explain WS posture, upper limb kinematics were calculated during the cocking and the acceleration phases of the serve. Shoulder internal rotation torque, wrist proximal and anterior forces ( P < .05) and elbow varus torque ( P < .01) were significantly higher in WS group, with no difference from NS group concerning serve velocity. Moreover, significant lower shoulder abduction and higher wrist extension ( P < .05) were observed for WS players during the cocking phase. Even if no significant difference was found between groups concerning injuries, higher upper limb joint loads suggested WS could be considered as pathomechanical in young elite players and could lead to upper limb joint injuries.